Organic carbon and silt determining subcritical water repellency and field capacity of soils in arid and semi-arid region - Mao, Jiefei; Li, Yaoming; Zhang, Junfeng; Zhang, Kun; Ma, Xuexi; Wang, Guangyu; Fan, Lianlian (Frontiers in Environmental Science, 2022)
Soil water repellency (SWR) is frequently observed in different types of land use and climates. Since SWR potentially enhances the difficulty of water infiltration in soil, the phenomenon can severely impact the water use of plants in arid regions. Therefore, understanding the origin of SWR is crucial in arid and semi-arid regions. This study investigated the fundamental and hydrological properties of soils in three arid ecosystems (desert, farmland, and forest). Analysis was done to determine any potential links between these properties, vegetation cover, and the severity of SWR. It was found that SWR was positively correlated with soil organic carbon (SOC), silt content, and field capacity of soil. The linear correlation and hieratical clustering analysis confirmed that the SOC on silt was the critical factor affecting the occurrence and persistence of SWR. The major source of organic carbon and nutrients to the soil was vegetation, which also had an impact on the distribution of soil carbon. The most striking observation was that the silt content was strongly correlated with both field capacity (r= 0.817, p= 0.001) and SWR (r= 0.710, p= 0.010), which can be attributed to the SOC on silt. The silt in arid and semi-arid regions had a relatively larger surface area and a much higher proportion as compared to the sand and clay, respectively. The results imply that silt could significantly affect the soil hydrological properties and that silt content could serve as a new proxy for predicting water repellency in arid and semi-arid regions.